Epidemiologic characteristics associated with ST23 clones compared to ST1 and ST47 clones of Legionnaires disease cases in France. (January 2015) - Cassier, P.; Campese, C.; Le Strat, Y.; Che, D.; Ginevra, C.; Etienne, J.; Jarraud, S.
Abstract: In France, approximately 1200 cases of Legionnaires disease (LD) are reported annually, and isolates are available for approximately 20% of cases identified since 2000. All Legionella pneumophila serogroup 1 (sg1) isolates are characterized by sequence-based typing at the National Reference Centre. LD cases caused by L. pneumophila sg1 reported from 2008 through 2012 were considered for the study. Our study objective was to describe cases according to their sequence type (ST). We also constructed multivariable modified Poisson regression models to estimate the incidence rate ratio (IRR) and to identify characteristics potentially associated with ST23 clones compared to ST1 and ST47 clones. We studied 1192 patients infected by ST1 ( n = 109), ST23 ( n = 236), ST47 ( n = 123) or other STs ( n = 724). The geographic distribution of the ST23 cases across the country was significantly different compared to other ST groups. This genotype was significantly associated with the absence of corticosteroid therapy compared to ST1 (IRR = 0.56; p 0.016). Concerning exposure, the ST23 genotype was significantly less associated with hospital-acquired infections compared to ST1 (IRR = 0.32; p 0.001), but it was more associated with infections acquired in hospitals and elderly settings compared with ST47. Finally, the ST23 genotype was less frequently associated with travel than other STs. Despite the large number of cases of ST23 infection, we did not identify any characteristics specific to this ST. However, we identified independent associations between ST1 and nosocomial transmission and steroid therapy. These findings should encourage further exploration, especially in terms of environmental diffusion, strain virulence and host factors.